Analisis Pengaruh Double Deck Primer Terhadap Fragmentasi Batu Kapur di Quarry D Blok 2 Lokasi 198 PT Indocement Tunggal Prakarsa Tbk. Citeureup Bogor - Jawa Barat - Franata Halomoan Sinaga; Raimon Kopa (Journals Mining Engineering : Bina Tambang, 2018)
Mining activities at PT Indocement Tunggal Prakarsa use the Quarry method and the process of dismantling the limestone material using blasting methods to meet the production targets and facilitate the loading and hauling process. Each blast requires a fragmentation size ≥ 90 cm of ≤ 5% and a ground vibration that fits the target of the company. However, the reality of the field found that the size of fragmentation does not exceed the target desired by the company because the size of ≥ 90 cm fragmentation of ± 11%. Improvements in blasting activities need to be done to obtain the size of the target fragmentation by the company. Therefore, one of the way to obtain the size of the target fragmentation is using the double deck primer methods by putting two primers in the bottom and in the centre of the blasting hole with stemming in the centre of the hole for minimalize the ANFO. The method resulting the same energy in all part of the hole and finally minimalize the boulder. The methods that are used to analyze fragmentation of explosive results in this research are theoretically by using Kuz-Ram method and image analysis method by using Split Desktop Software. This is done to determine the percentage of fragmentation of blasting results and take into account the boulder. The results of fragmentation analysis of the blasting results show that the addition of Double deck primer may affect the size of fragmentation. The sizes of fragmentation are ≥ 90 cm (boulder) to 2,27% and ground vibration at <2 mm / s so the size target of fragmentation that is desired by the company is achieved and the value of ground’s vibration  is under the value set by the company.Keywords:  Blasting, Fragmentation, Vibration, Cost